2016
DOI: 10.1111/cen.13090
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral aldosterone suppression and its resolution in adrenal vein sampling of patients with primary aldosteronism: analysis of data from the WAVES‐J study

Abstract: BAS sometimes occurs in AVS without ACTH stimulation. ACTH stimulation significantly reduces BAS with a single AVS procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Of these patients, we excluded those in whom we could not exclude the possibility of having unilateral hyperaldosteronism regardless of whether they were diagnosed with bilateral hyperaldosteronism according to AVS. We excluded patients with apparent bilateral aldosterone suppression, defined as lower aldosterone/cortisol ratios in the bilateral adrenal veins than that in the IVC [ 19 , 20 ]. We also excluded patients diagnosed with unilateral hyperaldosteronism using a repeat AVS or segmental AVS [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these patients, we excluded those in whom we could not exclude the possibility of having unilateral hyperaldosteronism regardless of whether they were diagnosed with bilateral hyperaldosteronism according to AVS. We excluded patients with apparent bilateral aldosterone suppression, defined as lower aldosterone/cortisol ratios in the bilateral adrenal veins than that in the IVC [ 19 , 20 ]. We also excluded patients diagnosed with unilateral hyperaldosteronism using a repeat AVS or segmental AVS [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wolley et al [ 8 ] reported that 2.6% of the patients who underwent AVS without adrenocorticotropic hormone (ACTH) administration showed the same phenomenon. Recently, we demonstrated using the data from the West Japan Adrenal Vein Sampling (WAVES-J) study that this phenomenon was observed in 9.5% of the patients who underwent AVS without ACTH administration, and that in 92% of these patients, it was resolved by ACTH administration [ 9 ]. In this study, we term this phenomenon as apparent bilateral aldosterone suppression (ABAS).…”
mentioning
confidence: 99%
“…7 In general, explanatory hypotheses of low aldosterone-tocortisol ratios in adrenal veins in PA are fluctuating aldosterone secretion, accidental superselective cannulation of a tributary vein draining only normal adrenal tissue, an ectopic production of aldosterone, or anomalous anatomy of the adrenal veins. 8 An anatomical study showed the presence of duplicate right adrenal veins in 2 of 83 cases, of which one emptied into the vena cava and one joined an accessory hepatic vein. 9 The adenoma contained a mutation in the ATP2B3 gene, which has been associated with PA. 10 It has been suggested that the steroid profile of the adrenal vein draining an APA-containing gland is specific for the presence of somatic mutations.…”
Section: A Pedunculated Aldosterone-producing Adenoma Drained By An Ementioning
confidence: 99%